2016
DOI: 10.1007/s11120-016-0291-5
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast avoidance movement as a sensitive indicator of relative water content during leaf desiccation in the dark

Abstract: In the context of global climate change, drought is one of the major stress factors with negative effect on photosynthesis and plant productivity. Currently, chlorophyll fluorescence parameters are widely used as indicators of plant stress, mainly owing to the rapid, non-destructive and simple measurements this technique allows. However, these parameters have been shown to have limited sensitivity for the monitoring of water deficit as leaf desiccation has relatively small effect on photosystem II photochemist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Recently, it was observed that blue-light-induced chloroplast movements are very sensitive to drought stress. Inhibition occurred already at RWC values considerably above 70%, and was, therefore proposed to be a sensitive tool for small changes in RWC (Nauš et al 2016). In typical C3 plants, critical leaf relative water content is about 70% and below this value non-stomatal effects occur.…”
Section: Question 25: What Do Chl a Fluorescence Measurements Tell Usmentioning
confidence: 99%
“…Recently, it was observed that blue-light-induced chloroplast movements are very sensitive to drought stress. Inhibition occurred already at RWC values considerably above 70%, and was, therefore proposed to be a sensitive tool for small changes in RWC (Nauš et al 2016). In typical C3 plants, critical leaf relative water content is about 70% and below this value non-stomatal effects occur.…”
Section: Question 25: What Do Chl a Fluorescence Measurements Tell Usmentioning
confidence: 99%
“…weighed again to obtain the turgid mass (Mt) and placed in a forced ventilation oven at 75°C until constant dry mass (Md). From these variables, the RWC was calculated as [RWC = ((Mf-Md) / (Mt-Md)) x100] (Nauš et al, 2016).…”
Section: Water Relationsmentioning
confidence: 99%
“…To explain these contradictory results we hypothesize that fluence rate during growth may affect the chloroplast relocation system in barley. The plants that did not show chloroplast movements (Maai et al 2011 ) were grown at PAR 4–5 times stronger than those in which the movements took place (Nauš et al 2016 and the present work). This explanation needs to be carefully validated as no correlation was found between excess light tolerance and the extent of chloroplast moments in several monocot and dicot species (Königer and Bollinger 2012 ).…”
Section: Discussionmentioning
confidence: 50%
“…In line with its role as a stress hormone, ABA appears to enhance plant sensitivity to light and promote the chloroplast avoidance response (Eckstein et al 2016 ). While Maai et al ( 2011 ) were unable to show chloroplast redistribution in barley ( H. vulgare ), avoidance movement in this species was reported 5 years later (Nauš et al 2016 ). According to our results both accumulation and avoidance responses are conspicuous in barley and in other C3 crop species that we have analyzed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation